Molecular Colony Diagnostics: Detection and Quantitation of Viral Nucleic Acids by In-Gel PCR. (July 2002) - Chetverina, Helena V.; Samatov, Timur R.; Ugarov, Victor I.; Chetverin, Alexander B.
When PCR is carried out in a polyacrylamide gel, each target molecule forms a molecular colony that comprises many copies of the original template. By counting the number of colonies, one can directly determine the target titer, with 100% of the DNA molecules and approximately 15% of the RNA molecules being detected. Furthermore, because of the spatial separation of the products in the gel, no interference is observed from another simultaneously amplified target even if it is present at a 10 6 higher amount or from human nucleic acids that outweigh the target by up to a factor of 10 12, which is often true of clinical samples. All these features provide for an accurate and reliable assay of viruses even at very low amounts, that is, in cases most important to diagnostics.